The Concept of Integrity in Teaching and Learning - Nillsen, R. (Journal of University Teaching and Learning Practice, 2005)
In this paper it is argued that the concept of integrity in aperson, or an activity, or an institution, is intimatelyconnected with notions of wholeness and completeness,and that the creation of integrity consists in developing anawareness of the possibility of greater wholeness andcompleteness, and in creating environments in which theymay occur. In a manner analogous to ethical integrity,integrity in inquiry, knowledge learning and teaching isseen as arising from a preparedness to submit oneself toa larger intellectual whole, in which one might say thatindividual preference is secondary to a “transcendingstate of affairs”. Some suggestions are made to helptowards progressing the ideals of integrity in teachingand learning, with some discussion in relation to specificdisciplines.